Profile of German senior tourists travelling on river cruise ships in the post-COVID period - Csaba Bíró (International Journal of Business and Social Science Research, 2023)
The German sending market has always been a major priority for domestic tourism in Hungary. For example, before the COVID-19 epidemic, Germany was ranked first among the outbound markets in terms of guest nights spent in commercial accommodation in 2019, with a share of 12.9%. The expenditure of German visitors traveling by Danube River cruise ships is also a determinant factor concerning destinations in Hungary. Due to their prominent role, we aimed to identify the main characteristics and preferences of German senior travellers arriving in Hungary, therefore, following the lifting of the pandemic-related travel restrictions, we conducted a personal survey of German visitors arriving from river cruise ships. Our findings revealed that interpreting 55+-year-old travellers as a homogeneous segment is a misconception, as they are highly heterogeneous. Therefore, we used factor analysis and cluster analysis to identify traveller groups within the segment and also included Barak and Schiffman's (1981) cognitive age scale to partly explain the difference in consumer preferences between self-reported age and chronological age. Linear regression modelling was also used to identify the extent to which differences in sending area location, destination preferences, and travel modes can shape spending. The study provides innovative results, both in theoretical and practical terms. Furthermore, the value of the research is enhanced by the inclusion of the guests of the most prominent German travel agencies in river cruising.